2005
DOI: 10.1097/01.brs.0000155423.18218.75
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Operative Complications in a Series of 471 Anterior Lumbar Interbody Fusion Procedures

Abstract: Placement of threaded devices, such as cages or bone dowels, was associated with a higher acute complication rate than was the placement of nonthreaded devices during anterior lumbar interbody fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
106
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 30 publications
2
106
1
2
Order By: Relevance
“…Complications associated with these traditional open spine fusion procedures have been described and include visceral injury and neurologic deficits. By virtue of the newer lateral transpsoas approach to the lumbar spine, an access surgeon is not necessary and the need to mobilize the great vessels is obviated, which minimizes the potential for visceral and vascular complications [4,10,22,26]. This advantage has been realized, with a recent clinical report of a zero incidence of intraoperative visceral injury [20].…”
Section: Discussionmentioning
confidence: 99%
“…Complications associated with these traditional open spine fusion procedures have been described and include visceral injury and neurologic deficits. By virtue of the newer lateral transpsoas approach to the lumbar spine, an access surgeon is not necessary and the need to mobilize the great vessels is obviated, which minimizes the potential for visceral and vascular complications [4,10,22,26]. This advantage has been realized, with a recent clinical report of a zero incidence of intraoperative visceral injury [20].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of adhesions after the primary surgery increases the potential for iatrogenic injury during the revision exposure [12]. If complications related to anterior exposure of the lumbar spine in primary surgeries have been well reported in the literature [1,5,19], only a few studies have reported the technical difficulties and the complications associated with revision surgeries through an anterior approach [2,9,11,[13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The complications associated with the anterior approach to the lower lumbar spine are summarized in Table 1. The incidence of vascular injury is estimated at 1.9-8 %, with the greatest risk at the L4-L5 level [3][4][5]. Ureteral injury during anterior lumbar arthrodesis has been reported in only a small number of cases [3,[5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, interbody arthrodesis is achieved through open surgical approaches, including anterior lumber interbody fusion (ALIF) [4,10,21,27,29,31], posterior lumbar interbody fusion (PLIF) [9], and transforaminal interbody fusion (TLIF) [8,18,24,27,35]. Several studies have documented the complications of these surgical techniques [1,5,11,23,30].…”
Section: Introductionmentioning
confidence: 99%
“…Anteriorapproach complications include damage to the abdominal organs (\ 1%), vascular injury (1.3%-15.6%), disruption of the sympathetic plexus (1.7%-13.3%), and postoperative ileus (0.6%-5.6%) [6,[29][30][31]. Posterior approaches avoid the aforementioned risks but can lead to soft tissue devitalization, nerve root injuries (9%-16%), postoperative radiculitis (6.7%-16.4%), and incidental durotomies (5.4%-10%) [5,9,26,31].…”
Section: Introductionmentioning
confidence: 99%